Diversity Of Predator And Parasitoids Insects On Several Types Of Oil Palm Plantation Ecosystems - Denal Putra Melketa; Benni Satria; Siska Efendi (Jurnal Riset Perkebunan, 2022)
Both oil palm plantations boerdering forests and oil palm plantations bordering rubber plantations were studied using purposive random sampling with pit fall traps, sweep nets and yellow pan traps. Species biodiversity was analyzed using the Shanon-Wienner index and the Simpson index. The dominant species was determined using the Important Value Index. This study found 1,683 individuals, 7 orders and 18 families of predatory and parasitoid insects. The Shanon-Wienner diversity index was 2.78 for oil palm plantations adjacent to forest and 2.62 for oil palm plantations adjacent to rubber plantations. While the Simpson diversity index was 1.00 for oil palm plantations adjacent to forest and 0.94 for oil palm plantations adjacent to rubber plantations. The Order Hymenoptera Family Formicidae had the highest Important Value Index (0.58 for oil palm plantations bordering forest and 0.62 for oil palm plantations adjacent to rubber plantations).